2009
DOI: 10.1007/s11010-009-0224-0
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic antibody to the α1-adrenergic receptor mobilizes intracellular calcium and induces phosphorylation of a cardiac 15-kDa protein

Abstract: Hypertension is a major cause for hypertrophic remodelling of the myocardium. Agonistic autoantibodies to extracellular loops of the alpha(1)-adrenergic receptor (alpha(1)-AR) have been identified in patients with arterial hypertension. However, intracellular reactions elicited by these agonistic antibodies remain elusive. An anti-peptide antibody (anti-alpha(1)) was generated against the second extracellular loop of the alpha(1)-AR that bound to its peptide epitope with high affinity (K (D) approximately 50 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Notably, this patient proved positive for agAAB to α 1 ‐AR but negative for agAAB to the β 2 ‐AR. The patient IgG elicited binding affinities towards the α 1 ‐AR loop1 peptide in the nanomolar range comparable to agAAB specific for the second extracellular loop of the receptor found in patients with refractory hypertension and to an antibody raised in rabbits against the putative receptor epitope [11, 20]. Our data from measurements of Ca i gave evidence for the presence of a α 1 ‐AR‐specific Ca i raising component in the patient IgG preparation.…”
Section: Discussionsupporting
confidence: 58%
“…Notably, this patient proved positive for agAAB to α 1 ‐AR but negative for agAAB to the β 2 ‐AR. The patient IgG elicited binding affinities towards the α 1 ‐AR loop1 peptide in the nanomolar range comparable to agAAB specific for the second extracellular loop of the receptor found in patients with refractory hypertension and to an antibody raised in rabbits against the putative receptor epitope [11, 20]. Our data from measurements of Ca i gave evidence for the presence of a α 1 ‐AR‐specific Ca i raising component in the patient IgG preparation.…”
Section: Discussionsupporting
confidence: 58%
“…In a parallel approach, rats were treated by intravenous injection of an antibody raised against the α 1 -AR peptide. This antibody we previously characterized to be agonistic and to act comparable to α 1 -AR antibodies from hypertensive patients [9], [15]. The intravenously injected α 1 -AR antibody raised in goat disappeared fast from the circulation of the rats.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, fibrosis was present in the hearts of immunized animals and not controls. Additional studies by Karczewski et al have raised α 1 -AR-AAs by immunizing rats with second loop peptides and have shown that these antibodies stimulate the mobilization of intra-cellular calcium stores [42]. These preclinical studies suggest that α 1 -AR-AAs may contribute to cardiovascular end-organ damage and hypertension.…”
Section: α1-adrenergic Receptor-activating Autoantibodies and Refractormentioning
confidence: 99%